SCHOOL PROGRAM FOR CREATING ONLINE BUSINESS ENTREPRENEURS TO IMPROVE THE QUALITY OF GRADUATES - Yulianti, Hana (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research is titled "Program Sekolah Pencetak Wirausaha Bisnis Online dalam meningkatkan Kualitas Lulusan SMK Muhammadiyah 1 Wonosobo." The research aims to determine how the use of social media as a business strategy by several online-based entrepreneurs impacts the graduates of SMK Muhammadiyah 1 Wonosobo. This research employs a quantitative descriptive method, and data collection is conducted using SWOT analysis techniques